The Comparison Extraction Methods of Crude Fat Content and Fatty Acid Profile of Eels (Anguilla marmorata (Q.) Gaimard) from Lake Poso - Jamaluddin; Ayu Putu Putriasih; Yonelian Yuyun; Agustinus Widodo (Journal of Pharmacy and Nutrition Sciences, 2019)
Eels (Anguilla marmorata (Q). Gaimard) from Lake Poso contain nutrition such as fatty acids EPA and DHA that are good for health. Extraction processes can be carried out to get the fats of these eels (Anguilla marmorata). This research aims to determine which one of the following extraction methods, namely: maceration and soxhletation, which is more appropriate to extract eels (Anguilla marmorata) so as to produce crude fats and the fatty acid profile with a higher content. The fatty acid profile was examined using the method of gas chromatography by converting results of the fat extraction into volatile fatty acid methyl esters. Research findings suggest that the obtained mean of crude fats was equal to 3.704% for the method of maceration and 28.872% for the method of soxhletation. Furthermore, results of the statistical testing analysis of the fatty acid profile generated a sig. a value greater than the 5% significance level, meaning that the content of fatty acids generated using the extraction method of maceration and that generated using the extraction method of soxhletation were not significantly different. This can be seen from the means of the fatty acid content, namely by 4.6956%, 9.6496%, and 1.5765% for the maceration method, and by 4.7287%, 9.338%, and 1.6646% for the soxhletation method. Based on the foregoing, it can be concluded that soxhletation is the appropriate extraction method.